THE ADAPTATION VS. STANDARDIZATION DILEMMA: THE CASE OF AN AMERICAN COMPANY IN BRAZIL - Rocha, Thelma Valéria; Silva, Susana Costa (Internext, 2012)
This study analyzes the adaptation versus standardization dilemma in International Marketing in subsidiaries of multinationals corporations. It highlights the importance of GMS – global marketing strategies – in the ability to innovate in subsidiaries in emerging economies, as Brazil. The objective is to find out how the level of autonomy displayed by subsidiaries influences the adaptation vs. standardization dilemma, and, consequently, the marketing-mix program. The methodology followed is qualitative research using a case-study approach in an American multinational from the food sector. In this case, we found out that firm’s brands are very important to this firm’s success overseas, which sustains that brand policies should be defined carefully at both levels: subsidiaries and headquarters. This brand policy influences direct the autonomy to innovate in marketing at subsidiaries level. This study is useful for managers at subsidiaries who need to understand the importance of global marketing strategies, and also for managers at headquarters who need to verify in which circumstances autonomy pays off.